How sociotechnical imaginaries shape consumers' experiences of and responses to commercial data collection practices. Issue 1 (2nd January 2023) - Sörum, Niklas; Fuentes, Christian
ABSTRACT: How is the ongoing "datafication" in society experienced by consumers? Critical discussions regarding the impact of datafication on consumers seldom study consumers' actual experiences. Conversely, the studies that do exist of consumers and their experiences of datafication tend to take an individualistic approach, arguing that how consumers experience and respond to the ongoing datafication is the result of their individual psychological make-up or the result of processes of cost–benefit calculations. Against that background, this article will instead show that the ways in which consumers experience and respond to datafication is linked to a number of broader sociotechnical imaginaries. Based on in-depth user interviews and drawing on previous work on sociotechnical imaginaries, this article develops an analysis of consumers' multiple imaginaries of data collection practices. Findings show that how consumers approach data collection operations is shaped by sociotechnical imaginaries that were both individually and collectively performed by consumers interacting with and using data-collecting devices.